Performance Audit of Integrated Child Development Services (ICDS) in Tripura (2014-2019) - CAG of India (CAG of India)
Integrated Child Development Services (ICDS) one of the flagship programmes of Government of India (GoI), launched in 1975 as an early childhood development programme is aimed at addressing health, nutrition and the development needs of young children, pregnant and nursing mothers. In order to address the gaps in implementation of the scheme, GoI repositioned ICDS as a Mission Mode programme in 2012, with appropriate institutional mechanisms at Central, State, District & Block levels, as well as adequate human and financial resources linked to accountability and outcomes. The Performance Audit of ICDS done by the Principal Accountant General (Audit), Tripura covering the period of 2014-15 to 2018-19 revealed the following: The Annual Project Implementation Plan (APIP) of the ICDS did not demonstrate a bottom-up, decentralised and participatory approach, so as to incorporate the roles of ICDS and Health functionaries at the district and village level. There was no evidence of involvement of local governance, institutions such as District Council and Village Panchayats in the planning process. The Performance Audit of Integrated Child Development Services (ICDS) revealed that the Department’s achievement of enrolment of beneficiaries under the ICDS, during the period 2014-19, was encouraging being 86 to 98 per cent during the period. However, the several deficiencies noticed during the Performance Audit of the Programme, in planning, management, execution as well as monitoring in implementation of the Programme, clearly indicated tremendous scope for improvement in programme implementation. The Department of Social Welfare and Social Education, which was responsible for the programme implementation, did not do Programme planning as per GoI guidelines. The Planning process was deficient in absence of decentralised planning with involvement of local bodies, trained professional experts and convergence with other State Programmes relating to health and sanitation. There was little involvement of the Village Health Sanitation and Nutrition Committees in the planning process. On review, we noticed that there was no institutional mechanism of data sharing and cross validation of data amongst the functionaries of ICDS (AWW) and NHM (ASHA, ANM).
For the Period 2014-15 to 2018-19